Speech to print: language essentials for teachers - Moats, Louisa Cook, 1944- (Baltimore : Paul H. Brookes Publishing Co., 2020)
"Since its publication in 2000, Speech to Print has become one of the most popular, highly regarded, and influential textbooks available on literacy instruction. In this third edition of her bestselling text, renowned literacy expert Louisa Cook Moats explains why effective language arts instruction must be informed by a deep understanding of spoken and written English--and how to apply this understanding to improve teaching practices. With dozens of focused chapter exercises, real-world examples, recommended teaching principles, and sample classroom activities, this book is an essential resource for any skilled teacher of reading and writing"--
Includes bibliographical references and index.
Keywords: Language arts (Elementary); Language arts teachers -- Training of